The Effect of Obesity on the Labor Market - Harpa Hrund Berndsen 1981- (2011)
INTRODUCTION: Obesity is a growing health problem in many countries, including Iceland. Obese people are at greater risk of several health problems, such as type II diabetes, heart disease, hypertension, stroke, knee and back problems and several types of cancers. The results of studies on the relationship between obesity and labor-market outcomes show negative effects for women, while the effects for men are limited. The aim of this study was mainly to examine the relationship between obesity and changes in employment status following the Icelandic economic meltdown of 2008. The relationship between income and obesity was also observed. METHODS: The data utilized in this study originates from a health and lifestyle survey “Heilsa og líðan Íslendinga” carried out by the Public Health Institute of Iceland in both 2007 and 2009. The sample is a stratified random sample of 9,807 Icelanders, ranging in age from 18 to 79. The net-response rate in 2007 was 60.8%. The participants from 2007 also received the 2009 version and 69.3% of them participated. A total of 42.1% of the original sample took part in the survey both in 2007 and 2009. Probit analysis was used when estimating the relationship between obesity and employment status, and an ordered probit analysis was used when observing the relationship between obesity and income. RESULTS: Obese women are more likely than their optimal weight counterparts to have lost their job following the economic crises in Iceland. The point estimates indicate that the relationship is also positive form men although it is not statistically significant. The point estimates of the analysis on the relationship between BMI and income indicate a negatively relationship for women, but a positive one for men. None of the estimates of the analysis on the data from 2009 were statistically significant. DISCUSSION: The relationship between obesity and job loss following the economic crisis is consistent with ex ante expectations. The results from the analysis of income are consistent with ...